The burning wire [compact disc, unabridged] : a Lincoln Rhyme novel - Deaver, Jeffery (Deaver, Jeffery. Lincoln Rhyme novel., 2010)
After a devastating explosion destroys a city bus, quadriplegic forensic criminologist Lincoln Rhyme is called to investigate. As the attacks continue, Rhyme and his team race to find whoever is responsible for the carnage. Meanwhile, Rhyme is also consulting on a case in Mexico, where a long-time nemesis, the Watchmaker, continues to elude authorities. With his health failing him, Rhyme must solve crack both cases before the body count rises.